The general principles of the rousseaunian state of nature: from human nature to civil society - Gómez Cantos, Juan Antonio (Revista de Filosofía, 2022)
This paper aims to explore the evolution of the social and politic theory of Jean-Jacques Rousseau. To this aim, I analyse the limits of his conceptual hypothesis, and introduce a comparison between what precedes the civil society (the state of nature itself) and what comes about it (the political construction of the social contract). In order to explain the theory, I will deepen into some aspects of Rousseau’s life, under the consideration that most of his political and social thoughts drink from the vital sources of the philosopher.